The Relationship Of Motor Educability And Motor Ability To Self Esteem In Physical Education Learning - Argie Manggala Octa Shakty; Tatang Muhtar; Adang Sudrazat (STKIP Muhammadiyah Kuningan, 2022)
This research is motivated by motor educability, and the motor ability of students is an essential factor in physical education learning. This study aims to determine the relationship between motor skills and motor skills on self-esteem in learning physical education. The method used in this research is descriptive quantitative with a dual paradigm design with two independent variables. This study used a sample taken by simple random sampling consisting of 70 student subjects at SMP Negeri 1 Tanjungsari in the 2021/2022 academic year. The research findings and discussion show that: 1) Motor educability has a significant relationship with students' self-esteem scores. The relationship between motor educability and student self-esteem is 97% or is at the level of a solid relationship. 2) Motor skills have a significant relationship to students' self-esteem. The relationship between motor skills and students' self-esteem is 98.4% or is at an extreme relationship level. 3) Motor and motor skills have a significant relationship to students' self-esteem. The relationship between motor educability and motor skills on students' self-esteem simultaneously or together is 98.6% or is at the level of a solid relationship. Motor skills have a significant relationship with students' self-esteem. The relationship between motor skills and students' self-esteem is 98.4% or is at the level of a solid relationship.